(untitled) (Bangladesh Pharmaceutical Journal, 2022)
The current study was conducted to assess the antioxidant, antimicrobial, cytotoxicity and thrombolytic potential of the leaves and stem bark of Erythrina fusca Lour grown in Bangladesh. For the assessment of antioxidant properties, DPPH scavenging and phosphomolybdenum assays were used. In the DPPH free radical scavenging assay, the chloroform soluble fraction of a methanol extract of leaves of E. fusca exhibited the highest free radical scavenging activity with an IC50 value of 5.5 ± 0.60 μg/ml, while the reference standard (ascorbic acid) showed an IC50 value of 5.8 ± 0.18 μg/ml. All the test samples and the standard BHT demonstrated good linear relationship in the phosphomolybdenum assay. It was observed that the test samples contained considerable number of bioactive compounds including total phenolics in the aqueous soluble fraction of the leaves giving the highest 94.02 ± 1.004 GAE/100g of dried sample. All test samples exhibited moderate antimicrobial activity against 13 Gram-positive and Gram-negative bacterial strains and 3 fungi, where the chloroform soluble fraction of the stem bark demonstrated the highest inhibition of growth with zone of inhibition of 19.3 ± 0.21 mm against Bacillus cereus. All the test samples displayed cytotoxic activity against brine shrimp nauplii having significant LC50 and LC90 values. The chloroform soluble materials demonstrated highest lethality with LC50 value of 1.55 ± 0.30 μg/ml and LC90 65.68 ± 0.23 μg/ml. On the other hand, the carbon tetrachloride soluble fraction of the stem bark showed the highest clot lysis (22.75 ± 0.59%) as compared to that (66.77 ± 0.61%) revealed by reference standard, streptokinase. The findings of this study revealed that the leaves and stem bark of E. fusca growing in Bangladesh possesses bioactive compounds but further studies are required to purify and identify them. Bangladesh Pharmaceutical Journal 25(1): 1-8, 2022 (January)